PENGARUH RASIO KEUANGAN TERHADAP POTENSI KECURANGAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Ira Hutahayan; Imam Ghozali (Diponegoro Journal of Accounting, 2025)
Fraudulent financial reporting is the intentional manipulation of financial statements by management to misrepresent a company's true financial condition, which may harm investors, regulators, and other stakeholders. One method to detect potential fraud is financial ratio analysis, as it provides early warning indicators of irregularities. This study examines the effect of leverage, profitability, and liquidity on the likelihood of financial statement fraud in banking companies listed on the Indonesia Stock Exchange (IDX) during 2021–2023. Using purposive sampling, 118 observations were analysed through logistic regression with IBM SPSS 27.The results of the study indicate that leverage has a positive and significant effect on the potential for financial statement fraud, while profitability has a negative and significant effect. Liquidity does not show a significant effect.